2015
DOI: 10.1007/s00345-015-1678-1
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral versus suprapubic catheter at robot-assisted radical prostatectomy: a prospective randomized trial with 1-year follow-up

Abstract: Draining the bladder with SPT only is a feasible option in patients undergoing RALP. Patients with SPT are significantly less bothered by the catheter at personal and genital hygiene compared to UC. The risk of BNC seems to be reduced in the SPT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…Our study demonstrated that there was no significant difference between the UC and ST group on postoperative pain at POD 7. The other three RCT studies showed similar result too [ 8 , 11 , 12 ]. Prasad et al stated that the most severe discomfort of catheter was experienced in the evening on surgery day due to bladder spasms induced by the presence of foreign body.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Our study demonstrated that there was no significant difference between the UC and ST group on postoperative pain at POD 7. The other three RCT studies showed similar result too [ 8 , 11 , 12 ]. Prasad et al stated that the most severe discomfort of catheter was experienced in the evening on surgery day due to bladder spasms induced by the presence of foreign body.…”
Section: Discussionsupporting
confidence: 61%
“…The characteristics of the included studies were shown in Table 1 . Among these studies, three were RCTs reaching the level of evidence 1b [ 8 , 11 , 12 ]. One cohort, non- randomized study reached the level of evidence 2b [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations